Fulfilling and desperately needed: Australian media representations of responses to homelessness. Issue 4 (26th January 2022) - Simpson Reeves, Laura; Clarke, Andrew; Kuskoff, Ella; Parsell, Cameron
Abstract: Homelessness is a significant social issue that continues to confront Australian society, despite burgeoning public and policy responses to the issue. Existing scholarship demonstrates the important role the media can play in shaping such responses by framing homelessness – and the people who experience it – in particular ways. However, to date there has been limited focus on how the media represents social responses to homelessness, or how such representations might influence public perceptions of the appropriateness of current responses. Drawing on analysis of four years of media articles (2016–2019), this article examines how the print media frames responses to homelessness in Brisbane, Australia. Our findings demonstrate that the media largely frames current responses as fulfilling and enjoyable for volunteers, and as desperately needed by people who experience homelessness. In representing the issue in this way, the media highlights the unequal power dynamics between those experiencing homelessness and those responding to homelessness. Rather than challenging this problematic power hierarchy, however, the media reifies it through its celebration of temporary and inadequate homelessness responses. We argue that such framing has the potential to promote public and policy support for responses that do little to address the underlying causes of the issue.